Intratumoral CD40 activation and checkpoint blockade induces T cell-mediated eradication of melanoma in the brain. Issue 1 (December 2017) - Singh, Manisha; Vianden, Christina; Cantwell, Mark; Dai, Zhimin; Xiao, Zhilan; Sharma, Meenu; Khong, Hiep; Jaiswal, Ashvin; Faak, Faisal; Hailemichael, Yared; Janssen, L.; Bharadwaj, Uddalak; et al.
Abstract CD40 agonists bind the CD40 molecule on antigen-presenting cells and activate them to prime tumor-specific CD8+ T cell responses. Here, we study the antitumor activity and mechanism of action of a nonreplicating adenovirus encoding a chimeric, membrane-bound CD40 ligand (ISF35). Intratumoral administration of ISF35 in subcutaneous B16 melanomas generates tumor-specific, CD8+ T cells that express PD-1 and suppress tumor growth. Combination therapy of ISF35 with systemic anti-PD-1 generates greater antitumor activity than each respective monotherapy. Triple combination of ISF35, anti-PD-1, and anti-CTLA-4 results in complete eradication of injected and noninjected subcutaneous tumors, as well as melanoma tumors in the brain. Therapeutic efficacy is associated with increases in the systemic level of tumor-specific CD8+ T cells, and an increased ratio of intratumoral CD8+ T cells to CD4+ Tregs. These results provide a proof of concept of systemic antitumor activity after intratumoral CD40 triggering with ISF35 in combination with checkpoint blockade for multifocal cancer, including the brain. Treatment options for metastatic melanoma are limited. Here the authors show that combining an immunostimulant adenovirus, currently in clinical trials for leukemia, with immune checkpoints blockade (ICB) results in systemic eradication of ICB resistant melanoma tumours from both skin and brain of mice.